Influence of physicochemical factors on the interaction of metallic nanoparticles with immune system cells - Sinai G. Gutiérrez-Cruz; Alejandro Muñoz-Diosdado; Ramón A. Gutiérrez-Calleja; Octavio Rodríguez-Cortés; Ana E. Ortiz-Reyez; Raúl Flores-Mejía (Frontiers in Nanotechnology)
Different physicochemical factors, such as size, concentration, shape, exposure time, area, and surface chemistry, influence the interaction between metallic nanoparticles (MNPs) and immune system cells. Particle size is particularly significant, as smaller particles facilitate easier cell internalization, while larger particles exhibit lower immunogenicity. Concentration also plays a critical role; high concentrations may trigger toxic responses, while low concentrations may act beneficially. Additionally, the morphology of nanoparticles affects their affinity for different cell types. It modulates the intensity of immune responses, while exposure time determines whether the immune response manifests as acute or chronic. The material composition of nanoparticles influences the initial interaction with cells, including protein adsorption and recognition by cell receptors. Understanding and controlling physicochemical factors is essential for developing therapeutic applications based on MNPs and minimizing potential adverse effects on the immune system. This paper reviews the reported biological effects of MNPs on various immune cell types, including B and T lymphocytes, neutrophils, monocytes, macrophages, dendritic cells, natural killer cells, mast cells, basophils, and eosinophils.